Copper-Catalyzed Sequential N-Arylation and Aerobic Oxidation: Synthesis of Quinazoline Derivatives - Liu, Qing; Zhao, Yufen; Fu, Hua; Cheng, Changmei (Synlett, 2013)
A novel and efficient copper-catalyzed cascade method for the synthesis of quinazoline derivatives has been developed. The protocol uses readily available substituted (2-bromophenyl)methylamines and amidine hydrochlorides as the starting materials, inexpensive CuBr as the catalyst, and economical and environment friendly air as the oxidant, and the corresponding quinazoline derivatives were obtained in moderate to good yields. The procedure underwent sequential intermolecular N-arylation, intramolecular nucleophilic substitution and aerobic oxidation.
Keywords: copper; N-arylation; aerobic oxidative; cascade reaction; quinazolines